2020
DOI: 10.3389/fonc.2020.01541
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Glasgow Prognostic Score and Modified Glasgow Prognostic Score as Biomarkers for Predicting Survival Outcome in Renal Cell Carcinoma

Abstract: Purpose: Accumulative studies suggest the Glasgow prognostic score (GPS) and modified Glasgow prognostic score (mGPS) to be potential biomarkers; however, their prognostic value remains debatable. Our meta-analysis focused on assessing the accurate prognostic value of GPS and mGPS in patients with renal cell carcinoma (RCC) in addition to their effectiveness. Methods: To investigate the relationship between mGPS/GPS and prognostic value in patients with RCC, we performed a comprehensive retrieval of relevant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“… 30 The elevated levels of CRP to more than 10mg/mL, combined with the levels of ALB decreased to less than 32 g/L indicated the highest HRs on survival. 31 Therefore, similar with other studies, 32 , 33 two key inflammation components, CRP and ALB contributed to the significantly higher predictive power of mGPS, compared with other inflammation-based indexes. These results provided insight into the relationship between inflammation and survival, serving the purpose of detailing prognostic information of mGPS.…”
Section: Discussionsupporting
confidence: 86%
“… 30 The elevated levels of CRP to more than 10mg/mL, combined with the levels of ALB decreased to less than 32 g/L indicated the highest HRs on survival. 31 Therefore, similar with other studies, 32 , 33 two key inflammation components, CRP and ALB contributed to the significantly higher predictive power of mGPS, compared with other inflammation-based indexes. These results provided insight into the relationship between inflammation and survival, serving the purpose of detailing prognostic information of mGPS.…”
Section: Discussionsupporting
confidence: 86%
“…The cut-off values for GPS are set at CRP 1.0 mg/dL and albumin 3.5 g/dL, and patients with CRP levels above 1.0 mg/dL and albumin levels below 3.5 g/dL are considered to have the poorest prognosis [39]. The usefulness of modified GPS (cut-off value of CRP = 0.5 mg/dL) has also been reported [40].…”
Section: Clinical Features For Anabolic Resistancementioning
confidence: 99%
“…Wang et al. indicated that baseline NLR can be regarded as a prognostic biomarker for NSCLC patients taking systemic therapy ( 13 ), and a higher GPS has been shown to correlate with poor clinical outcomes ( 14 ). The TIDE dysfunction score, which is related to tumor immune evasion, is an effective indicator of immunotherapy response and resistance ( 15 ).…”
Section: Introductionmentioning
confidence: 99%